Study on Some Physico-Chemical Characteristics and Heavy Metal Contamination of Powai Lake, Mumbai (India) - P. Ansari*, Shagufta; D. Irani, Shahin; Prabhu, D.V. (Asian Journal of Chemistry, 2014)
An objective of the present study to generate data from regular scientific study which will help to implement compatible policies and programme so as to gauge the extent of pollution of Powai lake (19° 8° N and 72° 54° E). The study was performed to understand the physico-chemical properties and heavy metal content in water of Powai lake, during month of March-April and August September 2014. The three sampling stations were selected on the basis of their importance. The samples collected from three different sites were analysed for physico-chemical parameters included pH, temperature, electrical conductivity, total dissolved solid, dissolved oxygen, chemical oxygen demand, biochemical oxygen demand. The study was also extended further to estimate level of toxic heavy metal viz., aluminium, arsenic, cadmium, cobalt, chromium, copper, iron, mercury, manganese, nickel, lead and zinc. The concentration of selected heavy metals were found by highly sensitive AAS-ICP- AES (atomic absorption spectroscopy, inductively coupled plasma, emission spectroscopy. The results indicate that there are some diverse contamination and pollution in Powai lake. Therefore, it is unsafe for domestic use hence needs a more attention for its sustainability factor.